Tradisi Kawin Lari (Merariq) pada Suku Bangsa Sasak di Desa Wanasaba, Lombok Timur - Muh. Muhsinin; Ni Luh Arjani; Ni Made Wiasti (Sunari Penjor : Jurnal of Anthropology, 2022)
This study analyzes the tradition of elopement (merariq) of the Sasak tribe in Wanasaba Village, East Lombok Regency. The merariq tradition is a tradition that exists in the marriage of the Sasak people. The merariq tradition is considered an extreme tradition among the people, especially those outside the island of Lombok. This study focuses on two problem formulations namely; first, how is the existence of the merariq tradition in Wanasaba Village and the impact of the merariq tradition on family life and social life in Wanasaba Village. The approach used in this research is qualitative with descriptive type and analysis with Nurture and Nature theory and feminism theory. The existence factors of merariq are economic, ceremonies in the merariq tradition, extreme merariq tradition debate, and disapproval or no blessing from parents both from the female parents and the male parents.